FÜTÜVVETİN KUTLU İÇEÇEĞİ ŞERBETE İŞLEVSEL BİR YAKLAŞIM - Aynur KOÇAK; Meriç HARMANCI (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2023)
When the historical processes of societies are followed, it is seen that rituals have a very important place, and many practices that have survived to the present day as social values are of ritual origin. Despite the formalities created by urban institutionalization processes, traditional ceremonies have maintained their place and continued to live in new beliefs. These activities, diversified mostly with the influence of mythic periods, are thought of as a mysterious spell, a blessed offering or an auspicious gift rather than a religious concern. The path of futuwwat, the boundaries of which we have not yet fully defined today, has also emerged as an area of spirituality that brings together the traditions of multicultural societies that have lived for hundreds of years after they met Islam. One of these traditions is the ritual of drinking salt water, also known as sherbet. Beings, objects and actions carry symbolic meanings and symbolic associations in addition to their conceptual equivalents. Unraveling the mystery of symbolic meanings not only enables us to reach beyond the visible, but also helps us to make sense and concretize. The rituals of drinking holy water and holy water, which we encounter since mythological texts, are kept alive in the form of drinking sherbet / salty water in the tradition of futuwwat. The aim of this study is to determine the origin, practice, and symbolic meanings of water and salt in the ritual of drinking salty water in futuwwatnames. It has been observed that sherbet, the combination of water and salt, which is indispensable for all societies with its symbolic meanings since mythic times, has also played an important role in many aspects of the initiation and initiation ceremonies of futuwwat.